Characterization of the aroma and colour profiles of fortified Muscat wines: comparison of Muscat Blanc “à petit grains” grape variety with Red Muscat - Jesus, Diva (2017)
Although Muscat Blanc “à petit grains” and Red Muscat grape varieties are both cultivated in the Douro Demarcated Region (Portugal), only Muscat Blanc is currently authorized for the production of the fortified wine “Moscatel do Douro”. The aim of this study was to evaluate the potential of the Red Muscat grape variety to be employed in the winemaking of Douro Muscat wines. Wines of both grape varieties were produced from the 2013 and 2014 harvests, and were chemically and sensory analysed 12 and 3 months after stopping the alcoholic fermentation, respectively. The Muscat Blanc “à petit grains” variety produced musts with higher sugar content than the red variety, but the final levels of sugar and ethanol were similar in all wines owing to the control of the fermentation time. Red Muscat wines presented higher concentrations of rose oxide and nerol than Muscat Blanc “à petit grains”; however, these differences were only significant in the youngest wines. Linalool and α-terpineol were found at higher levels in the 2013 Muscat Blanc “à petit grains” wines. No significant differences were found for the ester compounds, except for 2-phenylethanol, which was higher in the Red Muscat wines. The 12 months old wines presented a higher total concentration of esters than the younger wines. No significant differences were found for the higher alcohols composition between the two grape varieties. The chromatic analysis showed that, besides having a redder tone, Red Muscat wines had a higher colour intensity and a more pure/saturated colour than Muscat Blanc “à petit grains” wines. The sensory analysis did not detect significant differences in the aromatic and gustatory profiles between the two grape varieties. The Red Muscat grape variety shows great potential to be employed in the production of Muscat fortified wine either as monovarietal or in blends with Muscat Blanc “à petit grains”.